2018
DOI: 10.1038/gim.2017.170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of balanced chromosomal rearrangements previously unknown among participants in the 1000 Genomes Project: implications for interpretation of structural variation in genomes and the future of clinical cytogenetics

Abstract: PurposeRecent studies demonstrate that whole-genome sequencing (WGS) enables detection of cryptic rearrangements in apparently balanced chromosomal rearrangements (also known as balanced chromosomal abnormalities, BCAs) previously identified by conventional cytogenetic methods. We aimed to assess our analytical tool for detecting BCAs in The 1000 Genomes Project without knowing affected bands.MethodsThe 1000 Genomes Project provides an unprecedented integrated map of structural variants in phenotypically norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 37 publications
(80 reference statements)
1
65
0
1
Order By: Relevance
“…CNV detection and SV analyses were performed by our previously published methods (Dong et al, 2014;Dong et al, 2016;Dong et al, 2018a) with uniquely aligned reads/read-pairs. For CNV analysis, all aligned reads were classified into each adjustable sliding window (50-kb with 5-kb increments) for identifying the candidate region(s) with CNVs, then they were classified again into each non-overlapping window (5-kb) for detection of the precise breakpoints with the module of Increment-Rate-of-Coverage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNV detection and SV analyses were performed by our previously published methods (Dong et al, 2014;Dong et al, 2016;Dong et al, 2018a) with uniquely aligned reads/read-pairs. For CNV analysis, all aligned reads were classified into each adjustable sliding window (50-kb with 5-kb increments) for identifying the candidate region(s) with CNVs, then they were classified again into each non-overlapping window (5-kb) for detection of the precise breakpoints with the module of Increment-Rate-of-Coverage.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have demonstrated the feasibility and potential diagnostic utility of applying low-pass whole-genome sequencing (or genome sequencing, GS) analysis in the detection of CNVs (Dong et al, 2016;Dong et al, 2017) and chromosomal structural rearrangements (Dong et al, 2014) including balanced translocations and inversions in both clinical cohorts and presumably normal populations in the 1000 Genomes Project (Dong et al, 2018a;Dong et al, 2018b). By increasing the read-depth to a minimal of 30-fold for the purpose of including SNV/InDel detection, GS is able to provide comprehensive detection of various genomic variants, thus, providing a unique platform for gene discovery and potential clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The 10 ng stLFR-4 library also detected most of the deletions, but the three smallest were difficult to identify due to the lower coverage per fragment (and thus less barcode overlap) of this library. Long switch error rate 0.0020 0.0020 0.0020 To evaluate stLFR performance for detecting other types of SVs we made libraries from a cell line from a patient with a known translocation between chromosomes 5 and 12 (Dong et al 2016) and GM20759, a cell line with a known inversion on chromosome 2 (Dong et al 2017). stLFR libraries were able to identify the inversion and the translocation in the respective cell lines (Figure 2d-e).…”
Section: Structural Variation Detectionmentioning
confidence: 99%
“…The heterozygous deletion is found in a single haplotype. (D) Heat maps were also plotted for overlapping barcodes between chromosomes 5 and 12 for a patient cell line with a known translocation(Dong et al 2016) and (E) GM20759, a cell line with a known transversion in chromosome 2(Dong et al 2017).…”
mentioning
confidence: 99%
“…However, emerging studies have shown that at least 8.1% of those abnormalities routinely picked-up by karyotyping and chromosomal microarray analysis (CMA) would escape detection by this standard WGS 10 , letting alone those events beyond the resolutions. One of the reasons is that CNVs and SVs are predominantly mediated by repetitive elements (commonly >1 kb) 11 , causing the difficulty in identification of the flanking unique sequences by standard WGS 2,12,13 . To overcome this challenge 14 , sequencing of the junction sequences from large DNA fragments (i.e., 3~8kb) after circularization was introduced and named mate-pair sequencing 15,16 .…”
Section: Introductionmentioning
confidence: 99%